Spatial analysis to identify unauthorized municipal solid waste disposal sites in rural areas of southern Mexico - De la Rosa-Belmonte, Shirley Jhoanna (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2024)
The management of solid waste in rural areas of developing countries faces significant challenges due to economic constraints and irregular human settlements. These factors often lead to the creation of unauthorized disposal sites, which pose risks to human health, ecosystems and the economy. Remote sensing and geographic information system techniques provide a means to understand the complex issues associated with inadequate municipal solid waste (MSW) disposal. This study aimed to identify unauthorized disposal sites in the rural areas of southern Quintana Roo, Mexico, by examining land surface temperature (LST) and vegetation indices as potential indicators of unauthorized final disposal sites (FDSs). The findings reveal that 13% of the study areas have a high, moderate or low probability of hosting unauthorized disposal sites. Additionally, 3 authorized final disposal sites (FDSs) were confirmed, and 20 unauthorized sites were identified. LST and the normalized difference vegetation index were effective in detecting unauthorized sites, as these areas exhibited higher temperatures and less vigorous vegetation compared to adjacent areas. The results provide valuable insights into the issues associated with inadequate waste disposal in rural areas and offer information that can help optimize MSW management and mitigate its environmental and health impacts